Are Afghan Women More Polite than Men: Insights from “A Thousand Splendid Suns” - Jamal, Mujtaba; Nababan, Mangatur; Santosa, Riyadi; Djatmika, Djatmika (Universitas Muhammadiyah Semarang, 2024)
The novel “A Thousand Splendid Suns” is written by Khalid Hosseini, an Afghan American writer, about the lives of Afghans in Afghanistan. Considering the novel as a social semiotic, this paper intends to analyze the politeness strategies used by the two main characters: Mariam, the female protagonist, and Rasheed the male antagonist to conclude whether the female character is more polite or the male character. This paper is qualitative research, and it uses the theoretical framework of Penelope Brown and Stephen Levinson. The result of the paper indicates that both the characters used bald on record dominantly followed by positive politeness, negative politeness, and off record; also, the result indicates that women are more polite than men in the novel. It is because the female character used more off record and negative politeness than the male character. This paper adds to our knowledge of how the female and male characters are portrayed in the novel A Thousand Splendid Suns, and it also suggests that future researchers conduct ethnographic research to conclude about the politeness of the male and female in Afghan Society itself.